Keteladanan Guru Pendidikan Agama Kristen: Membangun Karakter Berlandaskan Iman - Riswan Riswan; Mersilina Ndruru (Sekolah Tinggi Alkitab Jember, 2025)
Teacher exemplarity in Christian religious education plays an important role in building students' character based on faith. Christian religious education does not only focus on theoretical instruction, but also on character formation through the example provided by teachers. This research aims to examine the role of teacher exemplarity in shaping students' Christian character in Christian religious education schools. The study employs a pure qualitative approach with a library research method. This method was chosen to analyze in depth the concept of Christian Religious Education teacher exemplarity in building student character based on comprehensive literature review. The research findings indicate that teacher exemplarity in Christian religious education holds a vital role in building students' faith-based character. As educators, teachers not only transfer knowledge, but also become living examples that reflect Christian values in daily actions. Through exemplarity in attitudes, behavior, and interpersonal relationships, teachers instruct students to live according to Christ's teachings, such as love, forgiveness, patience, and honesty. This exemplarity becomes the most effective tool in character formation because students tend to imitate what they see rather than merely what they hear. Keteladanan guru dalam pendidikan agama Kristen memainkan peran penting dalam membangun karakter siswa yang berlandaskan iman. Pendidikan agama Kristen tidak hanya berfokus pada pengajaran teori, tetapi juga pada pembentukan karakter melalui teladan yang diberikan oleh guru. Penelitian ini bertujuan untuk mengkaji peran keteladanan guru dalam membentuk karakter Kristiani siswa di sekolah-sekolah pendidikan agama Kristen. menggunakan pendekatan kualitatif murni dengan metode studi pustaka (library research). Metode ini dipilih untuk menganalisis secara mendalam konsep keteladanan guru Pendidikan Agama Kristen dalam membangun karakter siswa berdasarkan kajian literatur yang komprehensif. Hasil penelitian menunjukkan bahwa keteladanan guru dalam pendidikan agama Kristen memegang peranan yang sangat vital dalam membangun karakter siswa yang berlandaskan iman. Sebagai pendidik, guru tidak hanya mentransfer pengetahuan, tetapi juga menjadi contoh hidup yang mencerminkan nilai-nilai Kristiani dalam tindakan sehari-hari. Melalui keteladanan dalam sikap, perilaku, dan hubungan interpersonal, guru mengajarkan siswa untuk hidup sesuai dengan ajaran Kristus, seperti kasih, pengampunan, kesabaran, dan kejujuran. Keteladanan ini menjadi alat yang paling efektif dalam pembentukan karakter karena siswa cenderung meniru apa yang mereka lihat daripada sekadar apa yang mereka dengar.